Analisis Penggunaan Sistem Manajemen Mutu Iso/Iec 17025:2017 pada Laboratorium Pengujian Material Konstruksi Kabupaten Badung - I Putu Widyarsana; Putu Eny Suhardiyani (Syntax Corporation Indonesia, 2025)
Accreditation of ISO/IEC 17025: 2017 for laboratory is carried out to guarantee the testing quality conducted by a laboratory. The Badung Regency Construction Materials Testing Laboratory is one of the government laboratories that has implemented the SNI ISO/IEC 17025:2008 quality management system and has been accredited by KAN (National Accreditation Committee). To be able to continue accreditation from KAN, the laboratory plans to take acreditation of ISO / IEC 17025 version 2017. This study aims to analyze the implementation of Laboratory quality management system that is measured according to the clauses of ISO / IEC 17025: 2017 and to develop strategies that can be performed to improve the implemention of ISO / IEC 17025: 2017. In phase I, data collection was conducted through interviews using checklist developed based on ISO / IEC 17025: 2017. The implementation was assesed based on of the quality standards ISO / IEC 17025: 2017 (clause 4 to clause 8). The results showed that the implementation of ISO / IEC 17025: 2017 was in good category with score of 75,91%. While, atphase II, data collection was conducted through Focus Group Discussion (FGD) to develop strategies that can be performed by the company to succeed the implementation of ISO / IEC 17025: 2017. The identified strategies include rearranging documents of the laboratory task and authority of laboratory personnel related to organizational structure, responsibility, training of lab personnel, implementation of laboratory quality management systems, conducting risk analysis to determine risk management actions in each work procedure so that work processes can be more efficient to produce products and services according to requirements that meet customer satisfaction.